Psychological consequences of childhood obesity: psychiatric comorbidity and prevention - Rankin J; Matthews L; Cobley S; Han A; Sanders R; Wiltshire HD; Baker JS (Dove Medical Press, 2016)
Jean Rankin,1 Lynsay Matthews,2 Stephen Cobley,3 Ahreum Han,3 Ross Sanders,3 Huw D Wiltshire,4 Julien S Baker5 1Department of Maternal and Child Health, University of the West of Scotland, Paisley, 2MRC/CSO Social and Public Health Sciences Unit, Institute of Health and Wellbeing, University of Glasgow, Glasgow, Scotland; 3Department of Exercise and Sport Science, University of Sydney, Sydney, Australia; 4Cardiff School of Sport/Ysgol Chwaraeon Caerdydd, Cardiff Metropolitan University, Cardiff, UK; 5School of Science and Sport, Institute of Clinical Exercise and Health Science, University of the West of Scotland, Hamilton, Scotland Abstract: Childhood obesity is one of the most serious public health challenges of the 21st century with far-reaching and enduring adverse consequences for health outcomes. Over 42 million children <5 years worldwide are estimated to be overweight (OW) or obese (OB), and if current trends continue, then an estimated 70 million children will be OW or OB by 2025. The purpose of this review was to focus on psychiatric, psychological, and psychosocial consequences of childhood obesity (OBy) to include a broad range of international studies. The aim was to establish what has recently changed in relation to the common psychological consequences associated with childhood OBy. A systematic search was conducted in MEDLINE, Web of Science, and the Cochrane Library for articles presenting information on the identification or prevention of psychiatric morbidity in childhood obesity. Relevant data were extracted and narratively reviewed. Findings established childhood OW/OBy was negatively associated with psychological comorbidities, such as depression, poorer perceived lower scores on health-related quality of life, emotional and behavioral disorders, and self-esteem during childhood. Evidence related to the association between attention-deficit/hyperactivity disorder (ADHD) and OBy remains unconvincing because of various findings from studies. OW children were more likely to experience multiple associated psychosocial problems than their healthy-weight peers, which may be adversely influenced by OBy stigma, teasing, and bullying. OBy stigma, teasing, and bullying are pervasive and can have serious consequences for emotional and physical health and performance. It remains unclear as to whether psychiatric disorders and psychological problems are a cause or a consequence of childhood obesity or whether common factors promote both obesity and psychiatric disturbances in susceptible children and adolescents. A cohesive and strategic approach to tackle this current obesity epidemic is necessary to combat this increasing trend which is compromising the health and well-being of the young generation and seriously impinging on resources and economic costs. Keywords: pediatric obesity, psychological comorbidity, mental health, ADHD, depression, anxiety, obesity stigma, teasing, bullying